Methodological considerations in the use of systemic inflammatory indices for risk stratification in acute appendicitis - Qureshi, Ataah S.; Pereira, Darren L. (International Journal of Research in Medical Sciences, 2026)
Systemic inflammatory indices derived from the complete blood count, including the neutrophil-to-lymphocyte ratio, platelet-to-lymphocyte ratio, and systemic immune-inflammation index, have gained interest as low-cost adjuncts for diagnosing and risk-stratifying acute appendicitis. Using a recent retrospective study by Örün et al as an illustrative example, this commentary examines four recurring methodological issues in this literature: validation against a non-independent reference standard that shares laboratory input with the indices themselves; small subgroup sizes that yield imprecise discrimination estimates; substantial heterogeneity in proposed cut-off values across studies and populations; and incomplete reporting of effect sizes, such as regression coefficients presented without accompanying odds ratios or confidence intervals. These issues recur across much of the published literature, including existing systematic reviews and meta-analyses, and limit the extent to which encouraging single-study findings can be translated into validated bedside tools. We argue that future studies should validate these indices against independent reference standards such as histopathology, employ adequately powered analyses, pre-specify and externally validate cut-off values, and adhere to established reporting guidelines such as the TRIPOD statement. Addressing these structural weaknesses would strengthen the evidence base supporting the clinical adoption of systemic inflammatory indices in acute appendicitis.